Measurement of transient heat transfer in vicinity of gas–liquid interface using high-speed phase-shifting interferometer. (December 2017) - Kanda, Yuki; Shoji, Eita; Chen, Lin; Okajima, Junnosuke; Komiya, Atsuki; Maruyama, Shigenao
Abstract: The heat transfer process and initial stage of coupled convection at a gas–liquid interface are observed with high temporal and spatial resolutions in view of understanding phase transition dynamics such as evaporation or condensation for energy technologies. A high-speed phase-shifting interferometer is used to precisely measure the transient heat conduction and convection processes near the gas–liquid interface of a small water droplet. In the present study, the transient heat conduction around a water droplet interface during the adiabatic expansion process before the appearance of convection is visualized and examined. In the visualization experiment, transient density variations due to heat conduction in the vicinity of the gas–liquid interface are observed with temporal and spatial resolutions of 1 ms and 8.83 μm/pixel, respectively. It is determined that convection appears at approximately t  = 0.25 s in a fast depressurization process, while transitions in both temperature and pressure are observed. In addition, the transient density variations and distributions of the gas phase before convection are compared with numerical simulations as an optical path length difference, and there is good agreement between the simulations and experimental results. The measurement methods developed in this study can be applied in the measurement of interfacial heat and mass transfers with high temporal and spatial resolutions. Highlights: We study heat transfer and initial convection at a gas–liquid interface. We use high-speed phase-shifting interferometry to visualize heat transfer. The approach affords high spatial and temporal resolutions. We compare our results with numerical simulations. There is good agreement between calculations and experimental results.